1992
DOI: 10.1128/iai.60.8.3253-3261.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two genes encoding distinct transferrin-binding proteins in different Actinobacillus pleuropneumoniae isolates

Abstract: The gene encoding the ActinobaciUus pleuropneumoniae serotype 1 transferrin-binding protein (tfbA) was cloned, and the carboxy-terminal 70%o of the protein was expressed as an aggregate protein in Escherichia coli.The nucleotide sequences of the aJbA genes from A. pleuropneumoniae serotypes 7 (G.-F. Gerlach, C. Anderson, A. A. Potter, S. Klashinsky, and P. J. Willson, Infect. Immun. 60:892-898, 1992) and 1 were determined, and a comparison revealed that they had 65% sequence identity. The deduced amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 36 publications
3
30
0
4
Order By: Relevance
“…Interestingly, the complete sequence of the gonococcal TBP1 has domains homologous to Escherichia coli TonB-dependent outer membrane receptors, suggesting that the TBP1 molecule is a member of a class of proteins that serve as specific receptors for necessary nutrients such as iron and vitamin B~2 [13]. The deduced amino acid sequences of two distinct transferrin-binding proteins (TfbA) from different isolates of Actinobacillus pleuropneumoniae were also reported recently [14]. A comparison of the first 13 amino acids in the NH2-terminal of meningococcal TBP2 with those in the predicted NH2-terminus of the TfbA proteins shows about 60% sequence identity; the TfbA proteins possess a lipoprotein-like signal sequence.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the complete sequence of the gonococcal TBP1 has domains homologous to Escherichia coli TonB-dependent outer membrane receptors, suggesting that the TBP1 molecule is a member of a class of proteins that serve as specific receptors for necessary nutrients such as iron and vitamin B~2 [13]. The deduced amino acid sequences of two distinct transferrin-binding proteins (TfbA) from different isolates of Actinobacillus pleuropneumoniae were also reported recently [14]. A comparison of the first 13 amino acids in the NH2-terminal of meningococcal TBP2 with those in the predicted NH2-terminus of the TfbA proteins shows about 60% sequence identity; the TfbA proteins possess a lipoprotein-like signal sequence.…”
Section: Discussionmentioning
confidence: 86%
“…2). When the Tbp2 sequences of the eight H. influenzae strains were compared with those of the N. meningitidis strains B16B6 and M982 (Legrain et al, 1993), N. gonorrhoeae strain FA19 (Anderson et al, 1994) and A. pleuropneumoniae strains 205 and 37 (Gerlach et al, 1992b), minimal similarity was found (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the Tbp2 amino acid sequences of H. influenzae strains Eagan (MinnA sequence is identical), DL63, PAK 12085, SB12, SB29, SB30, and SB32, N. meningitidis strains B16B6 and M982 (Legrain et al, 1993), N. gonorrhoeae strain FA19 (Anderson et al, 1994), and A. pleuropneumoniae strains 205 and 37 (Gerlach et al, 1992b). The single letter amino acid code is used and stop codons are designated by asterisks.…”
Section: Figmentioning
confidence: 99%
“…1992), Pathogenic bacteria have adapted to this iron-limiting environment by developing highly specific and effective iron-assimilation systems. A large number of these bacteria secrete siderophores -smail, non-protein iron cheiatots which, because ot their extvemety high aftinity tor iron(ill), scavenge trace amounts of iron(lll) from the environment and shuttle the iron back to the bacterial cell (Baggs and Neilands, 1987;Braun and Hantke, 1991), Some bacteriai pathogens, like neisseriae (Archibald and DeVoe, 1979;Mickelsen et at., 1982: Dyer ef a/., 1987, Haetnoptiilus inftuenzae (Coulton and Pang, 1983;Schtyvers, 1988;Jarosik et at.. 1994), Vibrio ctiolerae (Stoebner and Payne, 1988;Henderson and Payne, 1994), yersiniae (Stojiljkovic and Hantke, 1992) and Actinobaciltus ptearopneumotiiae (Gerlach et at., 1992) have evolved more sophisticated mechanisms to sequester iron from the host. These pathogens can directly bind the host's ironbinding proteins such as lactoferrin, transferrin, and haem-containing compounds, and use them as sole sources of iron, Neisseriae meningitidis is one of the leading causes of bacterial meningitis in children and heaithy adults in the worid.…”
Section: Introductionmentioning
confidence: 99%